GEREJA SEBAGAI UMAT TEBUSAN ALLAH YANG BERDAMPAK BAGI KOMUNITAS - Sitanggang, Tahan (JURNAL IMPARTA, 2024)
The church that has been redeemed by Jesus Christ must have a life that grows both in faith and in the practice of that faith. Pentecostals live the stages of Christianity called the Fivefold Gospel. The Christian life of Pentecostal people must have an impact that is realized in the practice of social life (community).